1982
DOI: 10.1111/j.1365-2125.1982.tb04971.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the responses of human isolated arteries and veins to noradrenaline.

Abstract: Chloramphenicol in the newborn infant. A physiological explanation of its toxicity when given in excessive dose. New Engl. J. Med., 262, 787-794. system do not change with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The pitfalls of expressing the response to norepinephrine as a percentage of the maxi mum response to potassium [11,19] have been previously addressed [19]. Since aging does not necessarily influence the response to both stimulants similarly [ 19; fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pitfalls of expressing the response to norepinephrine as a percentage of the maxi mum response to potassium [11,19] have been previously addressed [19]. Since aging does not necessarily influence the response to both stimulants similarly [ 19; fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several au thors [4,5,8,19,36] have wrestled with this issue, and it has yet to be resolved. In recog nition of this, some authors [4,8] have pre sented their data in more than one way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, depres sion of cardiac adrenergic responsiveness is a feature of aging apparently shared by both man and rat [Kreider et al, 1984], In terms of the vasculature, substantial similarities between man and rat in the effect of age have also been documented. Sensitivity to norepinephrine of arteries isolated from hu mans ranging from 30 to 83 years of age does not change with age [Stevens et al, 1982]; this has also been shown to be true in the rat [Duckies et al, 1985], Analysis of concentration-response curves to norepi nephrine in the carotid and femoral arteries shows that sensitivity to alpha-adrenergic stimulation does not change with age from 6 to 27 months. The concentration of nor epinephrine to produce 50% of a maximal response (EC50) was constant with age.…”
mentioning
confidence: 94%
“…Owing to the lack of plasma catecholamine data, the mechanism of the exaggerated pressure response and vasoconstriction in middle-aged subjects could not be solved. However, the maximum response to norepineph rine in blood vessels was found to be increased with age in rats [ 19], whereas aging had no effect on responsiveness to norepinephrine in larger arteries in men [20],Therefore, the exaggerated pressure response immediately after smoking in middle-aged subjects seemed to be due to aadrenergic receptor stimulation induced by nicotine.…”
Section: Discussionmentioning
confidence: 92%